Dendrite-free deposition on lithium anode toward long-life and high-stable Li//graphite dual-ion battery. Issue 58 (1st July 2019) - Xi, Xiao-Tong; Feng, Xi; Nie, Xue-Jiao; Hou, Bao-Hua; Li, Wen-Hao; Yang, Xu; Yang, Ai-Bo; Sun, Wen-Dong; Wu, Xing-Long
Abstract : Following modification with a carbon nanofibers film, an advanced Li//graphite dual-ion battery shows superior cycle life with dendrite-free Li anode. Abstract : Metallic lithium protection plays a crucial role on improving the electrochemical properties of Li-anode-based batteries. Herein, for an advanced Li//graphite dual-ion battery, constructing a robust and conductive film of carbon nanofibers on a Li anode effectively achieves dendrite-free Li growth and hence significantly enhances the long-life cyclic stability.